PENGASUHAN ORANGTUA DAN PENALARAN MORAL: KAJIAN META-ANALISIS - Pratiwi, Margaretha Maria Shinta; Subandi, Subandi; Adiyanti, Maria Goretti (Universitas Muhammadiyah Jember, 2020)
Research on the relationship between parenting with moral reasoning has been done by many researchers because of the increasing of moral decadence problem. Various studies about parenting with moral reasoning showed varying results. Research on parenting style with moral reasoning also showed varying results. The purpose of this study is to determine the relationship between parenting with moral reasoning through the meta-analysis study. Total studies used were 20 articles with 72 studies with 15 343 subjects. Meta-analyzes were done based on the calculation of sampling error and measurement error. The results of meta-analyzes indicate that generally there is a correlation between parenting to moral reasoning is low (?=0,04). The impact of sample error of 29.97%. Results of a meta-analysis of the types of parenting styles showed that parenting style such as authoritative, authoritarian, and permissive had a relationship with moral reasoning. The results of the research grouping by type of parenting style showed different results on the correlation results with moral reasoning. Authoritative parenting style (?=0,046) had a greater correlation than authoritarian parenting styles (?=0,015) and permissive (?=-0,038).